Informational Efficiency, Interest Rate Variability, and Central Bank Operations. (IMF Working Papers; Working Paper ;, 1997)
It is shown how the frequency of central bank intervention in financial markets can affect the incentives for economic agents to acquire information, which will be reflected in market prices and thus become available to policy makers. The optimal frequency of intervention, and therefore the optimal interest rate variability, will balance the desirability of attaining given operational targets against the benefits of encouraging informational efficiency. The ability of the central bank to send clear signals of its own intentions will also depend on market informational efficiency.